Human TNFα-induced protein 3-interacting protein 1 (TNIP1) promoter activation is regulated by retinoic acid receptors - Gurevich, Igor (2012)
Coregulator proteins play key roles in transcriptional control by members of the nuclear receptor superfamily. Previously, we demonstrated that tumor necrosis factor α (TNFα)-induced protein 3-interacting protein 1 (TNIP1) is a corepressor of agonist-bound retinoic acid receptors (RARs). Additionally, TNIP1 has been shown to repress peroxisome proliferator-activated receptors (PPAR) and NF-κB activity and interact with HIV proteins nef and matrix. TNIP1 transcriptional regulation, however, is under studied. Here we show that under permissive epigenetic conditions, TNIP1 expression is induced by all trans retinoic acid (ATRA). Within a 6000bp region of the human TNIP1 promoter we cloned, both proximal and distal promoter regions are RAR responsive with the latter having RA response elements (RAREs) recognizable by their sequence and functionality in native promoter and synthetic RARE luciferase constructs, EMSA, and ChIP assays. These findings suggest a feedback loop whereby RARs activate expression of TNIP1, which then attenuates their activity. Together with anticipated constitutive transcription factors and the previously described NF-κB-responsiveness of the proximal TNIP1 promoter, the expected combinatorial control of TNIP1 expression could likely modulate TNIP1’s impact in any of its target pathways. The degree of control by RARs or other transcription factors would in turn depend on their cell-specific level of expression and/or activation from signals in the environment such as ATRA and TNFα.